(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Bangladesh has one of the largest diabetic populations in the world and its Rajshahi region has distinct geographical and cultural identity. Determinants and basic defects of the disorder which vary substantially among populations due to racial and environmental heterogeneity. Materials & Methods: This study was conducted to characterize the new patients attending the Rajshahi Diabetic Center which gives an idea about the proportion and risk indicators of DM among people in the Rajshahi region. It was a hospital based observational analytic study with a hybrid research strategy having both cross-sectional and nested case-control designs. A multistage sampling technique was followed with 660 subjects. Results: Out of the total subjects attending the OPD of RDC for the first time, 65% were found to suffer from T2 DM. mostly (75%) of middle age (37% within 30-40 yrs and 37% within 41-50 yrs), only 2% cases had age <30 yrs and 23% had age >51yrs. The mean ±SD calorie consumption (2549±637) of the diabetic subjects was higher than that in non-T2 DM subjects and it came mainly from CHO (59.3%) and fat (55.9%). 47.3% of subjects were normal weight, 36.1% over weight and 16.6% obese. Fasting serum Insulin was significantly higher in the T2 DM group as compared to non-T2DM (Serum Insulin level µIU/ml, M±SD) (13.5±4.9) subjects (p=<0.001). HOMA%B was (37±17) significantly lower in the T2 DM subjects as compared to non-T2 DM subjects. HOMA%S was (41±13) significantly lower in the T2 DM subjects as compared to non-T2 DM subjects. Conclusion: Both (HOMA%B) and (IR) constitute the basic defects of diabetes in Rajshahi population, but (HOMA%B) seems to be more predominant in these subjects. (HOMA%B) in Rajshahi population is associated with males and level of education and insulin resistance (IR) is associated with males and daily CHO intake. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 131-137